2009
DOI: 10.1007/s11856-009-0115-9
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Kakeya-type problems and small bases

Abstract: A subset U of a group G is called k-universal if U contains a translate of every k-element subset of G. We give several nearly optimal constructions of small k-universal sets, and use them to resolve an old question of Erdős and Newman on bases for sets of integers, and to obtain several extensions for other groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…As remarked above, for r large the bound of Theorem 4 (and consequently, that of Corollary 5) is rather weak. The best possible construction we can give in this regime does not take linearity into account and is just a universal set construction where, following [ABS09], we say that a subset of a group is k-universal if it contains a translate of every k-element subset of the group. As shown in [ABS09], every finite abelian group G possesses a k-universal subset of size at most 8 k−1 k|G| 1−1/k .…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As remarked above, for r large the bound of Theorem 4 (and consequently, that of Corollary 5) is rather weak. The best possible construction we can give in this regime does not take linearity into account and is just a universal set construction where, following [ABS09], we say that a subset of a group is k-universal if it contains a translate of every k-element subset of the group. As shown in [ABS09], every finite abelian group G possesses a k-universal subset of size at most 8 k−1 k|G| 1−1/k .…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…The best possible construction we can give in this regime does not take linearity into account and is just a universal set construction where, following [ABS09], we say that a subset of a group is k-universal if it contains a translate of every k-element subset of the group. As shown in [ABS09], every finite abelian group G possesses a k-universal subset of size at most 8 k−1 k|G| 1−1/k . In our present context the group under consideration is the additive group of the vector space F n q , in which case we were able to give a particularly simple construction of universal sets and refine slightly the bound just mentioned.…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…Similarly, if m is at least n 1/2+ then almost all m-element sets require a basis of size at least c √ n. For the borderline case when m is of the order √ n their counting argument only yields existence of sets that need a basis of size c √ n log log n/ log n, and they asked if every m-set of size m = √ n has a basis with o(m) elements. This is established in [7], where it is shown that in fact any such set has a basis of size O( √ n log log n/ log n). The argument is probabilistic.…”
Section: Additive Number Theorymentioning
confidence: 90%
“…. , n} is of size Ω(n 1− ) for every > 0 and d ≥ 2, only a modest improvement of the n 2/3−o(1) lower bound of Erdős and Newman for large values of d is proved in [7], where it is shown that the set {t d : t = 1, . .…”
Section: Additive Number Theorymentioning
confidence: 99%
“…Certainly, multiplicative energy E × (A, B) can be expressed in terms of multiplicative convolutions, similar to (1). Usually we will use the additive energy and write E(A, B) instead of E + (A, B).…”
Section: Notationmentioning
confidence: 99%